The complexity of care for the thermal control of the premature infant - Aimone Carneiro de Oliveira; Climene Laura de Camargo; Maria Carolina Ortiz Whitaker; Lucas Amaral Martins; Laiane Farias Santos; Emanuela de Almeida Oliveira; Larissa de Carvalho Silveira (Universidade Federal do Ceará, 2023)
Objective: to understand the perception of nurses about the complexity of care for thermal control of the premature infant. Methods: qualitative study conducted with 13 nurses from a public maternity hospital, through virtual interviews, with semi-structured script, submitted to Content Analysis and interpreted by the theoretical support of the complex adaptive care system model. Results: the factors present in nurses' care in thermal control of premature infants are related to the complexity permeated by environmental factors such as the temperature of the unit and distribution of air conditioning currents; institutional factors such as the availability and correct use of technologies, and those related to the professional, such as performance, training, and qualification. Conclusion: adjusting the temperature of the unit; better distribution of the air conditioning currents;availability of technologies; a policy of continued education in the service; training in handling the equipment; supervision and requirement for preventive and corrective maintenance of the devices can influence the reduction of thermal instability events in premature infants. Contributions to practice: stimulating professional qualification, planning of intersectoral actions for technological structuring and preventive maintenance of the units, systematization of assistance to premature infants in thermal control minimizing risk of neonatal morbimortality due to thermal instability.